2012
DOI: 10.1007/s00167-012-2265-2
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the posterior cruciate ligament is not helpful in highly conforming mobile-bearing total knee arthroplasty: a randomized controlled study

Abstract: The preservation of the PCL was not helpful for improving kinematics and clinical outcome in highly conforming mobile-bearing TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…5 articles described how the randomization sequence for the study was generated ( Misra et al 2003 , Chaudhary et al 2008 , Harato et al 2008 , Roh et al 2013 , Thomsen et al 2013 ). The method of concealment of allocation was reported in 6 studies ( Chaudhary et al 2008 , Harato et al 2008 , Kim et al 2009 , Seon et al 2011 , Matsumoto et al 2012 , Thomsen et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…5 articles described how the randomization sequence for the study was generated ( Misra et al 2003 , Chaudhary et al 2008 , Harato et al 2008 , Roh et al 2013 , Thomsen et al 2013 ). The method of concealment of allocation was reported in 6 studies ( Chaudhary et al 2008 , Harato et al 2008 , Kim et al 2009 , Seon et al 2011 , Matsumoto et al 2012 , Thomsen et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Roh et al [ 31 ] comparing highly conforming PCL-retaining vs. PCL-sacrificing MB knees, there were kinematic differences between both procedures, however, with no consequences in terms of significant differences in ROM, functional scores or radiographic results. In the present study, all patients received a PCL-retaining TKA, with no outcome differences when comparing both groups across the time.…”
Section: Discussionmentioning
confidence: 99%
“…Knee flexion range is a useful measure and accurate indicator of TKA outcomes. Previous clinical studies have reported mean final knee flexions ranging from 100° to 130°, regardless of the surgical technique or prosthetic design [32,40,42].…”
Section: Introductionmentioning
confidence: 99%